Recognition and protection of refugees in Malaysia - Ishan Jan, Mohammad Naqib; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (Moment Publications, 2018)
Malaysia possesses a great reputation for allowing refugees to live in the country until they repatriate or resettle in a third country. People - who came to Malaysia due to wars, armed conflicts, political conflicts, and persecution in their country of origin - need to approach the United Nations High Commission for Refugees (UNHCR) for the formal recognition as refugees. They can be recognised as refugees by the UNHCR after undergoing through a lengthy interview process to determine whether they are genuine refugees. However, they are not legally recognised in Malaysia due to the fact that Malaysia is not a party to the 1951 Convention Relating to the Status of Refugees (1951 Convention) and also the 1967 Protocol Relating to the Status of Refugees (1967 Protocol). Besides, there is no specific domestic law dealing with the protection and rights of refugees. Accordingly, refugees are exposed to various kinds of exploitations while waiting for the repatriation to their own country or resettle in a third country. Sometimes, the waiting period may well be over a decade due to numerous reasons. Therefore, this papers aims at identifying existing legal frameworks that can be applicable for the protection of refugees in Malaysia. In addition, authors also explore whether it is time for Malaysia to become a party to the 1951 Convention. Alternatively, this issue can also be addressed by enacting a local statute for protecting refugees in Malaysia without becoming a member to the 1951 Convention.